Two new Cumella (Crustacea: Cumacea: Nannastacidae) from the North Pacific, with a key to the North Pacific Cumella - Gerken, Sarah (Zootaxa, 2009)
Two new species of Cumella (Cumacea: Nannastacidae), C. oculata and C. alaskensis are described from shallow Alaskan rocky shores. The new species C. oculata can be distinguished from other North Pacific Cumella by the combination of a large eye lobe, no spines dorsally on the carapace, and carapace without large tubercles. The new species C. alaskensis can be distinguished from the other North Pacific Cumella by the 5 spines distributed unequally on the dorsal crest.